PENGEMBANGAN MODUL ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œPEDULI IBU HAMILÃƒÂ¢Ã¢â€šÂ¬Ã‚Â DI DESA SUMBEREJO BANYUPUTIH SITUBONDO - Dewi Andariya Ningsih (LPPM Universitas Abdurrab, 2020)
Maternal mortality) is one of the important indicators of the degree of public health. The goals of health development that will be achieved in 2030 is the increase in the degree of public health, one of which is indicated by the decrease AKI indicator. In the Strategic plan of Ministry of Health 2015-2019 which confirms the Indonesian healthy Program through the family approach is a Program that supports the movement of healthy Living Community (GERMAS) Puskesmas Banyuputih follow up the program To make the innovation Program you want to maintain health should be able. Referring to the program then researchers make the development of the care module pregnant mothers consisting of family standby, healthy souls and recognize the signs of early pregnancy danger in the village Sumberejo Banyuputih Situbondo compiled in the form of modules. This research uses research and development methods or better known as Research and Development. The research subject used by researchers is all II and III trimester pregnant mothers who meet the criteria of inclusion and exclusion and are willing to be the subject of research. The results showed that the majority of respondents amounting to 83.3% (25 people) experienced increased knowledge and no declining knowledge. After research, there is an impact on increasing the knowledge of pregnant women because of the many advantages of the pregnant women care module that can improve the knowledge of mothers and increase the insight of pregnant women around pregnancy information